Wiedza na temat autyzmu wśród obecnych i przyszłych pedagogów a dylemat wspólnego kształcenia i integracji w wymiarze edukacyjnym = Knowledge of autism among the present and future educators, and the dilemma of common education and integration in the educational dimension - Chrzanowska, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper is an attempt to diagnose the state of knowledge of autism among educators, special educators and students of education. This is particularly important, especially nowadays, when the idea of inclusive education is not only becoming the tendency of educational solutions in Poland , but it soon will be authorized by law (in September 2012 the President of Poland shall sign the Convention on the Rights of Persons with Disabilities, which guarantees them the possibility of integration. In the document, the so-called "inclusive education" is considered a priority which is to counteract exclusion.).
Keywords: autyzm; edukacja włączająca; inkluzja społeczna; pedagogika; edukacja